2019
DOI: 10.1111/jvp.12817
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic profiles of meloxicam after single IV and PO administration in Bilgorajska geese

Abstract: The purpose of this study was two‐fold: I) to determine the pharmacokinetic profile of meloxicam (MLX) in geese after intravenous (IV) and oral (PO) administration and II) to assess tissue residues in muscle, heart, liver, lung, and kidney. Ten clinically normal female Bilgorajska geese were divided into two groups (treated, n = 8; control, n = 2). Group 1 underwent a 3‐phase parallel study with a 1‐week washout period. In phase I, animals received MLX (0.5 mg/kg) by IV administration; the blood was collected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 26 publications
2
15
0
Order By: Relevance
“…However, if the procedure or injury involves pain, changes in behavior, posture, and temperament are observed in the bird (Hawkins & Paul‐Murphy, 2011; Machin, 2005). Non‐steroidal anti‐inflammatory drugs (NSAIDs) are particularly used in cases of arthritis and lameness developed as a result of degenerative joint disease and traumatic injuries (Malik & Valentine, 2018; Sartini et al, 2020a). Cyclooxygenase (COX) enzymes have been found in poultry, and prostaglandins (PG) are involved in the pain process (Hawkins & Paul‐Murphy, 2011; Machin, 2005).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, if the procedure or injury involves pain, changes in behavior, posture, and temperament are observed in the bird (Hawkins & Paul‐Murphy, 2011; Machin, 2005). Non‐steroidal anti‐inflammatory drugs (NSAIDs) are particularly used in cases of arthritis and lameness developed as a result of degenerative joint disease and traumatic injuries (Malik & Valentine, 2018; Sartini et al, 2020a). Cyclooxygenase (COX) enzymes have been found in poultry, and prostaglandins (PG) are involved in the pain process (Hawkins & Paul‐Murphy, 2011; Machin, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Only the pharmacokinetics of meloxicam were reported from NSAIDs in geese (Sartini et al, 2020a). Because of the low potential for side effects of tolfenamic acid in different animal species and its valuable pharmacokinetic properties such as high bioavailability and long elimination half‐life (Corum et al, 2018, 2019; Raweewan, Chomcheun, et al, 2020; Raweewan, Laovechprasit, et al, 2020), it can also be preferred to be used for geese as a NSAID.…”
Section: Introductionmentioning
confidence: 99%
“…However, the obvious differences in t 1/2ʎz of MLX, CRP, and TA have been reported among species. After IM and oral administration in quails, the t 1/2ʎz of MLX was 1.55 and 1.59 h, respectively, which was similar to that previously reported in flamingos (oral: 1.83 h, Lindemann et al, 2016), shorter than that previously reported in parrots (IM: 15.1–35.3 h, oral: 15.8–33.6 h, Molter et al, 2013; Montesinos et al, 2016), penguins (IM: 31.87 h, oral: 28.59 h, Morrison et al, 2018), zebra finches (IM: 3.24 h, Miller et al, 2019), hawks (oral: 3.97 h), owls (oral: 5.07 h, Lacasse et al, 2013), and geese (oral: 3.65 h; Sartini et al, 2020), and longer than that previously reported in cockatiels (oral: 0.90 h, Dhondt et al, 2017) and vultures (IM: 0.42 h, oral: 0.32 h, Naidoo et al, 2008). After IM and oral administration in quails, the t 1/2ʎz of TA was 1.51 and 1.25 h, respectively, which was shorter than that previously reported in mammals (IM: 2.61–8.22 h, oral: 5.13–19.7, Corum et al, 2018; Sidhu et al, 2005; Sidhu et al, 2006; Dinakaran & Dumka, 2013) and reptiles (IM: 22.49–53.69 h, Corum et al, 2019a; Raweewan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…MLX has been successfully used in managing postoperative pain and arthritis in birds (Cole et al, 2009; Desmarchelier et al, 2012). The pharmacokinetics of MLX has been studied in a number of bird species, including chickens, ostriches, ducks, turkeys, pigeons (Baert & Backer, 2003), geese (Sartini et al, 2020), parrots (Molter et al, 2013; Montesinos et al, 2016), flamingos (Lindemann et al, 2016), penguins (Morrison et al, 2018), zebra finches (Miller et al, 2019), hawks, owls (Lacasse et al, 2013), cockatiels (Dhondt et al, 2017), and vultures (Naidoo et al, 2008). MLX has shown highly variable pharmacokinetic properties with the bioavailability of 11–104% and elimination half‐life of 0.32–35 h following extravascular administration in birds (Dhondt et al, 2017; Molter et al, 2013; Montesinos et al, 2016; Naidoo et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the support of independent scientists results of paramount importance in order to expand the knowledges even in niche areas of the veterinary field. Recent examples of that have been reported in geese ( Sartini et al., 2020a , 2020 b , 2021a ,2021 b , 2021 c , 2022b ) and crocodiles ( Poapolatep et al., 2017 ; 2020a ,2020 b , 2020 c , 2020 d , 2022a , 2022b) both considered minor species at global level. A long series of drugs have been tested by independent scientists introducing new important data in animals that have been ignored so far.…”
mentioning
confidence: 94%